Analysis of Portuguese Wines by Fourier Transform Infrared Spectrometry (Ftir) - Moreira,J. L. (2002)
The aim of this work is to present the results of the experimental optimisation of the essays with FTIR, supported by analytical data obtained by the methods that the laboratory routinely applies. The use of FTIR in Enology -an emergent and very promising methodology -must be based on specific analytical calibrations established through the quantification by usual physical and chemical methods of the parameters to analyse. The global calibration obtained for the analysis of wines allows good results for all parameters. The specific calibration performed leads, in the case of the total sugars, to more adjusted results to the values given by the analytical methods in routine, being the use of a general or specific calibration indifferent for the remaining studied parameters